Trauma-related aggression - Dissociation or psychosis - John E Berg (Open Journal of Trauma - Peertechz Publications, 2019)
Psychosis, dissociation or simple aggression may have similar clinical presentations. A case in a resident facility for trauma treatment is presented and discussed. Getting triggered by someone often happens in patients with dissociative disorders after childhood traumatization, rarely so in psychosis. Aggressive acts may also be seen without apparent connection to trauma.